EFFECTS OF MASTERY LEARNING AND SELF-MANAGEMENT STRATEGIES ON LEARNING OUTCOMES IN CIVIC EDUCATION AMONG SENIOR SECONDARY SCHOOL STUDENTS IN IBADAN, NIGERIA (2016)
Civic education builds students attitudes, morals and values necessary for good citizenship and effective life in the society. The academic performance of Senior Secondary School (SSS) students in Civic Education (CE) has been on the decline in recent past which has resulted in moral decadence and alarming incidence of social vices such as rape, cultism, unwanted pregnancies and addiction to social media. Previous studies have centred on the utilisation of conventional methods to foster academic achievement and positive attitude in CE with little efforts on new strategies for enhancing learning outcomes among secondary school students. This study, therefore, determined the effects of Mastery Learning (ML) and Self-Management Strategies (SMS) in enhancing learning outcomes (academic achievement and attitude) in CE among public SSS students in Ibadan. It also examined the moderating effects of gender and Academic Self-Concept (ASC). Bloom taxonomy model provided the theoretical framework while pretest-posttest control group quasi experimental design with a 3 x 2 x 3 factorial matrix was used. Multistage sampling procedure was used. A simple random sampling technique was used to select three local government areas (LGAs) from the eleven LGAs in Ibadanland. Three SSSs were randomly selected from the three LGAs within Ibadan municipality. Ninety SS II students were randomly selected from the participants from the three selected secondary schools. This consisted of 45 male and 45 female participants. The participants were randomly assigned to the two treatment and control groups and exposed to eight-week training of ML and SM strategies. Civic Education Achievement test ( = 0.75), Students‟ Attitude to CE Questionnaire ( = 0.72), Academic Self Concept scale ( = 0.67) and Learning Preference Assessment ( = 0.87) were used for data collection. Data were subjected to Analysis of covariance and Duncan Post hoc test at 0.05 level of significance. There was significant main effect of treatment on students‟ academic achievement (F(2,74) = 3.65 partial 2 = 0.43) and attitude (F(2,74) = 3.21;2 = 0.56) to CE. Mastery Learning Strategy (64.97) had highest mean score followed by those in Self-management strategy (58.53) and control (53.77). The mean score on attitude to CE of participants exposed to MLS (102.56) was significantly different from those in SMS (100.36) and control (87.73). There was no significant main effect of ASC on academic achievement and attitude to CE. There were no significant main effect of gender on academic achievement and attitude to CE. The two and three-way interaction effects of treatment and gender and treatment, academic self concept and gender on both achievement and attitude to CE were not significant. Mastery learning strategy was more potent in enhancing learning outcomes in Civic Education among senior secondary school students in Ibadan metropolis than self-management strategy. Educational psychologists and teachers should adopt the two strategies to enhance students learning outcomes in Civic Education. Keywords: Mastery learning strategy, Self-management strategy, Academic Achievement and attitude to civic education. Word count: 464